Massive pulmonary embolism in pregnancy: intra-arrest thrombolysis and resuscitative hysterotomy - Taylor, John Edward Ashbridge (BMJ Case Rep, 2020)
Massive pulmonary embolism (PE) is a leading cause of maternal death and may require intra-arrest thrombolysis as well as resuscitative hysterotomy. The case presented is a primigravida in her mid-30s at 28 weeks gestation. The patient presented to the emergency department after out-of-hospital cardiac arrest. Return of spontaneous circulation (ROSC) was achieved but not sustained. Episodic cardiopulmonary resuscitation with epinephrine boluses was required. Resuscitative hysterotomy was performed intra-arrest. Echocardiography revealed a dilated right heart consistent with massive PE and thrombolysis was administered. ROSC was obtained thereafter and output was sustained. Subsequent CT brain revealed irreversible hypoxic injury. Treatment was withdrawn with the support of family. Postmortem examination confirmed massive PE. Thrombolysis can restore and improve cardiovascular status in cardiac arrest caused by massive PE. Thrombolysis is not contraindicated in maternal resuscitation where resuscitative hysterotomy may also be required.